Disease assessment and management of the vasculitides. - Luqmani, R; Exley, A; Kitas, G; Bacon, P (1997)
The improvement in survival with chemotherapy has resulted in a change of the natural history of the systemic vasculitic syndromes. The vasculitides are now viewed as chronic disease rather than fatal conditions. Their course is frequently characterized by relapse as well as the scars of irreversible organ damage from disease and drug toxicity. Assessment tools are available which can serve as outcome measures in clinical trials as well as a guide to better management of individual patients. Improvements in therapy in future are dependent on a better understanding of the pathogenesis of these conditions and the ability to assess disease accurately.